The Impact of Implementation of a Joint Liability System on Member Behavior: (Case Study in Setia Bhakti Wanita East Java, Women’s Cooperatives) - Iwang Suwangsih; Nuzulul Fatimah; Noneng Rukayah Sukatmadiredja; Emmywati (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
This study analyzes the impact of the consistent implementation of a joint liability system in cooperative life. This research uses descriptive qualitative research methods using in- depth interview techniques which are then carried out by open coding to find patterns and theories related to the results of the interviews. As said by Miles & Huberman (1992: 19) there are three stages that must be done in analyzing qualitative research data, namely (1) data reduction; (2) exposure data (data display); and (3) drawing conclusions and verification (conclusion drawing / verifying). The results of the analysis of this study that have been carried out, explain that cooperative members who implement and obey the rules that exist in joint liability cooperatives unconsciously have an impact on their behavior changes, they have discipline and a high sense of solidarity towards other members.